Peran Teknologi Informasi Dan Komunikasi Dalam Pengelolaan Pendidikan Menengah Pasca Pandemi Covid-19 - Ahmad Zain Sarnoto (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2022)
Improving high-level thinking skills (high-order thinking) has become an essential requirement This article raises a study of the role of information and communication technology in the management of secondary education after the Covid-19 pandemic, bearing in mind that the Covid-19 pandemic has changed the governance of education in general, including secondary education. On the other hand, the government implemented a distance learning policy (PJJ) and reduced face-to-face learning (PTM) at the start of the pandemic. In these conditions and situations, information and communication technology (ICT) is considered very important. Although in reality, there are many obstacles, such as low human resources, lack of infrastructure, and geographical conditions. From there, online and offline learning is often the best choice. This type of research is qualitative. The approach used is an educational management approach. Data is collected from library sources. The theory used to analyze the data is the blended learning theory. This study found three main aspects; first, the issue of using ICT is partial, where school institutions that are human, social, cultural, and infrastructure ready will benefit significantly from ICT. Vice versa. Second, the presence of the government's role in offering solutions to the problem of education management is also partial. ICT is not optimal because government support is not holistic, it is even dysfunctional when faced with old problems of educational institutions, such as lack of infrastructure and geographical problems. Third, the role of ICT in education management is ambiguous, between as a solution to a problem and as a compulsion amidst the limitations of the school institution itself. The findings of this study are helpful as an enrichment in the study of secondary education management disciplines, on the other hand as a form of criticism and input to managers of educational institutions.